Analysis and Implementation of Comparison Between Podman and Docker in Container Management - Husain, Husain; Marzuki, Khairan; lauw, Christopher Michael; Azhar Mardedi, Lalu Zazuli (International Journal of Electronics and Communications Systems, 2023)
The increasing use of the internet makes the implementation process more accessible, but the problem is that it is difficult to manage network management, with the emergence of container technologies such as Docker and Podman as efficient application management solutions. This research compares Docker and Podman regarding container management using the Network Development Life Cycle (NDLC) methodology. This study evaluates three parameters: accessing the Fedora project registry, handling images or ISOs, and user access in containers. The results show that Podman performs better regarding registry access, is slightly faster with images, and offers faster user creation. Overall, the study concludes that Podman is superior, demonstrating compatibility with Docker and proving its efficacy in container management.